A Study of the Nonlinear Optical Properties of Stilbazolium Derivative Crystal - Ribeiro, Lucas Figueiredo; Baseia, Basilio; Valverde, Clodoaldo (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2020)
In this report we start from ab initio calculations to get the structural properties of an isolated molecule of an organic crystal. Since the knowledge of the effects of neighboring molecules their study became necessary for an appropriated description of nonlinear optical properties in the solid state and more efficient design of such materials requires theoretical models that describes in detail the structural and electronic properties of the crystalline environment. The derivative of an organic stilbazolium single crystal, (E)-1-ethyl-2-(4-nitrostyryl) pyridin-1-ium iodide (NSPI); the NSPI crystallizes in the centric triclinic system with the P1space group. Here the dipole moment, the linear polarizability, and second hyper polarizability of the asymmetric unit of the compound were investigated through a super molecule approach in combination with an iterative scheme. In this approach the electrostatic interactions of the atoms of molecules embedded are represented by point charges. In addition to these calculations, other interesting results are obtained when we compare the results for isolated molecule and the molecule under the influence of its crystalline environment (embedded molecule); under such an influence we find a very interesting result for the average 2nd hyperpolarizability: 290,000% higher in the isolated molecule when compared to the embedded one.